MiR-143HG Gene Polymorphisms as Risk Factors for Gastric Cancer in Chinese Han Population - Liu, Jianfeng; Li, Haiyue; Liu, Yuanwei; Sun, Yao; Wu, Jiamin; Xiong, Zichao; Li, Bin; Jin, Tianbo (Current Molecular Medicine, 2020)
Background: MicroRNA (miRNA) is a pivotal regulator of the occurrence and development of various cancers. And gastric cancer (GC) is one of the most common and deadly cancers in the world. The aim of this study is to explore whether the microRNA-143 host gene (miR-143HG) polymorphisms are correlated with the risk of GC. Methods: 5 single-nucleotide polymorphisms (SNPs) were genotyped among 506 patients and 500 healthy controls in Han Chinese population. Multiple genetic models, stratification analysis and haplotype analysis were used to evaluate the association between miR-143HG polymorphisms and GC risk by calculating odds ratios (ORs), 95% confidence intervals (CIs). Results: Our results indicated that rs11168100 was associated with decreased risk of GC under the Codominant model (OR = 0.67, 95%CI = 0.52-0.88, p = 0.003), and under the Dominant model (OR = 0.72, 95%CI = 0.56-0.92, p = 0.009). Rs353300 was associated with increased risk of GC under the Recessive model (OR = 1.41, 95%CI = 1.06-1.87, p = 0.017). Further, rs11168100 and rs353300 were correlated with the susceptibility of GC (age > 60 years), and three SNPs (rs12654195, rs353303, and rs353300) were related with the risk of GC (age ≤ 60 years). In addition, two SNPs (rs12654195 and rs11168100) were found to be associated with decrease in the susceptibility of GC in the female subgroup. Rs353300 represented two-sided roles in the occurrence and development of GC in female. Finally, rs3533003 was associated with decreased risk of GC in stratified analysis of lymph node metastasis. Conclusion: For the first time, our results provide some evidence on the polymorphisms of miR-143HG associated with GC risk in the Chinese Han population.
Keywords: Chinese Han population